Exploring spatial indicators for biodiversity accounting. (November 2016) - Remme, Roy P.; Hein, Lars; van Swaay, Chris A.M.
Highlights: Biodiversity accounting structurally measures changes in biodiversity components. We assess applicability of species diversity indicators within the SEEA framework. We spatially analyse richness, abundance and presence of rare species. Applicability of indicators for accounting was assessed based on eight criteria. For comprehensive biodiversity accounts multiple indicator types should be analysed. Abstract: In the context of the System for Environmental-Economic Accounting, biodiversity accounting is being developed as a tool to monitor and increase the understanding of human impacts on biodiversity. Biodiversity accounting aims to structurally measure, monitor and map changes in multiple biodiversity components, as an integral part of a larger system of ecosystem accounts. Both indicators relevant for ecosystem functioning and indicators that reflect the non-use values of biodiversity can be included in biodiversity accounting. In this paper we focus on the latter, and we test the potential applicability of a set of species indicators for developing a biodiversity account in Limburg province, the Netherlands. In particular, we map and analyse a range of indicators reflecting species richness, the presence of rare and threatened species and species diversity. We test spatial correlation to identify the minimum set of indicators that would need to be included in the account. We also evaluate individual indicators using eight different criteria. We show that, in Limburg province, a set of indicators covering at least five species groups is required, and that it would be most meaningful to have indicators reflecting the occurrence of threatened species. However, data availability as well as the most suitable set of indicators are likely to differ between areas, and case studies in other countries are required to support the selection of indicators for biodiversity accounting in an international framework.